Expressões do racismo ambiental no bairro Santa Maria em Aracaju-SE - Silva, Rafaela dos Santos (2022)
The present study aims to analyze expressions of environmental racism associated with the presence of solid waste deposits in the surroundings of housing regions in the Santa Maria neighborhood, in the city of Aracaju SE. In this sense, this work calls into question the unveiling of the concept of environmental racism in its materialization from bibliographic data. The qualitative data discussed are present in academic productions about the Santa Maria neighborhood that address aspects of the proposed object. 7 dissertations and 3 articles were found that address data on solid waste in Aracaju, with only 3 dissertations and 2 articles corresponding directly to the research categories. In view of this, we observe that environmental racism is present in the historical elements of the occupation of the Santa Maria territory, as well as in the current characterization of the neighborhood, as described in the analyzed productions.